Monitoring the assembly–disassembly–organisation–reassembly process of germanosilicate UTL through in situ pair distribution function analysis. Issue 35 (20th August 2018) - Henkelis, Susan E.; Morris, Samuel A.; Mazur, Michal; Wheatley, Paul S.; McHugh, Lauren N.; Morris, Russell E.
Abstract : A study into the disassembly and organisation steps of the ADOR process has been undertaken through in situ Pair Distribution Function (PDF) analysis. Abstract : A study into the disassembly and organisation steps of the ADOR process has been undertaken through in situ Pair Distribution Function (PDF) analysis. Three aqueous systems (water, 6 M HCl and 12 M HCl) were introduced to a parent zeolite germanosilicateUTL in a cell. Hydrolysis could be clearly seen whenUTL was exposed to water over a period of 8 h, forming the disorder layered material, IPC-1P. In hydrochloric acid, the hydrolysis step is too quick to observe and a Ge–Cl containing species could be seen. In 6 M HCl, the rearrangement of the interlayer region began after an induction period of 8 h, with the process still occurring after 15 h. In 12 M HCl, the rearrangement appears to have come to an end after only 6 h.